2017
DOI: 10.1093/femsle/fnx236
|View full text |Cite
|
Sign up to set email alerts
|

Peptide transporter YjiY influences the expression of the virulence gene mgtC to regulate biofilm formation in Salmonella

Abstract: Formation of a biofilm is one of the coping strategies of Salmonella against antimicrobial environmental stresses including nutrient starvation. However, the channeling of the starvation cue towards biofilm formation is not well understood. Our study shows that a carbon starvation gene, yjiY, coding for a peptide transporter, influences the expression of a virulence-associated gene mgtC in Salmonella to regulate biofilm formation. We demonstrate here that the mutant strain ΔyjiY is unable to form a biofilm due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…sodA downregulation suggests that these cells are prone to ROS assault. Previous study has shown that YjiY depletion upregulates mgtC leading to bio lm defect 14 . Interestingly, we observed downregulation of mgtC, implying that the bio lm inhibition by ΔyjiY sup and the inherent bio lm defect of ΔyjiY strain follow different mechanisms.…”
Section: Discussionmentioning
confidence: 94%
“…sodA downregulation suggests that these cells are prone to ROS assault. Previous study has shown that YjiY depletion upregulates mgtC leading to bio lm defect 14 . Interestingly, we observed downregulation of mgtC, implying that the bio lm inhibition by ΔyjiY sup and the inherent bio lm defect of ΔyjiY strain follow different mechanisms.…”
Section: Discussionmentioning
confidence: 94%
“…1A ), which was absent in the supernatant of the strain where yjiY was trans-complemented in a plasmid (STM Δ yjiY:pQE60-yjiY) . Previous study showed that Δ yjiY is a biofilm deficient strain (14). To check whether the biofilm inhibitory property is specific to Δ yjiY supernatant, we inoculated WT strain with biofilm deficient strain Δ csgD ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…sodA downregulation suggests that these cells are prone to ROS assault. A previous study from our group showed that YjiY depletion upregulates mgtC leading to biofilm defect (14). Interestingly, we observed downregulation of mgtC , implying that biofilm inhibition by Δ yjiY supernatant and the inherent biofilm defect of the Δ yjiY strain follow different mechanisms.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Virulence genes are consequently important for bacterial infection and pathogenesis. The expression of virulence genes has been found to be affected by several factors such as nutrient starvation (Chandra et al, 2017;Paytubi et al, 2017); concentrations of NaCl (Larsen & Jespersen, 2015), oxygen (Melson & Kendall, 2019), and glucose (Valdes et al, 2018); temperature (Guijarro et al, 2015); growth phase (Koohsari et al, 2017); kind of carbon source (Ferrando et al, 2014;Kentache et al, 2016); pH (Do et al, 2019); sodium glycocholate (Joffre et al, 2019); and L-glutamine (Haber et al, 2017).…”
Section: Introductionmentioning
confidence: 99%